Adoption of Islamic financing: The case of MSMEs in Indonesia - Novianto, Abdullah Syakur; Pratikto, Heri; Soetjipto, Budi Eko; Djatmika, Ery Tri (The Economics and Finance Letters, 2025)
This study aims to investigate the role of non-economic factors that can influence MSMEs' financial decisions in Indonesia. The data was analyzed using partial least squares. 320 MSMEs participated in a questionnaire survey that was used to gather data. The findings demonstrated that behavioral intentions to adopt Islamic funding are positively impacted by attitudes. If MSMEs believe that the Sharia financial products offered are beneficial to improve MSMEs' performance, then their attitudes towards Sharia financing will be positive. Subjective norms influence behavioral intentions to adopt Islamic financing positively. The behavioral intentions to adopt Islamic funding can be impacted by coworkers, friends, and family. The behavioral intentions to adopt Islamic financing are positively impacted by perceived behavioral control. The realization of a person's intention to choose Islamic financing depends on the ability and accessibility possessed by the individual according to his/her capacity. It was discovered that the desire to adopt Islamic financing was influenced both directly and indirectly by the mediating attitudes for the relationship between pricing fairness and religiosity and behavioral intentions to embrace Islamic financing. The findings of this study extended the TPB model by adding religiosity and price fairness to Islamic financing.